The Role of Wearable Devices in Tracking the Well-Being of Patients Suffering from Chronic Conditions - the review - Jakubczyk, Natalia; Leszczyńska-Knaga, Elżbieta; Kurowski , Marek; Kuczapska , Karolina; Gliwa , Anna; Ryglewicz, Monika; Fabian , Dariusz; Kwaśniewska, Paula; Moczydłowski , Paweł; Michalczuk, Karolina (Journal of Education, Health and Sport, 2025)
In recent years, wearable technology, including smartwatches, fitness bands, and smart rings, has become an integral part of health monitoring for patients with chronic diseases. These devices enable non-invasive, continuous tracking of key health parameters such as heart rate, glucose levels, sleep quality, and physical activity. This article analyzes their application in managing diabetes, cardiac arrhythmias, depression, and chronic obstructive pulmonary disease (COPD), highlighting their benefits in early detection of abnormalities and personalized healthcare. Research indicates that these tools significantly enhance treatment results while minimising the likelihood of complications and supporting patient self-management. Despite numerous advantages, such as increased patient engagement, this technology faces challenges, including data privacy and integration with healthcare systems. The conclusions point to the necessity for further development of wearable devices to ensure their broader implementation in clinical practice and patients’ daily lives.